SPE Annual Technical Conference and Exhibition 2012
DOI: 10.2118/159090-ms
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Stratigraphic Parameters from Well Test Data in Turbidite Reservoirs

Abstract: Well test analysis in turbidite reservoirs is complicated by the intricate stratigraphy prevailing in this depositional environment. Because of this complexity, important reservoir architectural parameters driving flow behavior (e.g., shale drape coverage, object dimensions) cannot be estimated using simple analytical reservoir models employed in conventional well test analysis techniques. Alternatively, simulation-based well test analysis offers the advantage of being able to capture stratigraphic complexity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…0.39m × 0.39m). Local grid refinement is performed to produce accurate well test profiles (Chen et al, 2012).…”
Section: Impact Of the Fine-gridding In Simulation Resultsmentioning
confidence: 99%
“…0.39m × 0.39m). Local grid refinement is performed to produce accurate well test profiles (Chen et al, 2012).…”
Section: Impact Of the Fine-gridding In Simulation Resultsmentioning
confidence: 99%
“…In wells B, C and D, the ¼ slope straight line in the pressure derivative starts earlier and further investigation is required. Chen et al (2012) suggested that the complexity of the depositional environment in turbidite reservoirs cannot be estimated using conventional analytical models but can be captured by numerical simulation of the well test. In this study, a systematic methodology for numerical simulation of the well test analysis was followed: …”
Section: Transition Effect Of Characteristic Flow Regimesmentioning
confidence: 99%
“…Now that it is established that there are no barriers between the horizontal wells from the modified pulse tests and possible areal anisotropy, plausible geological features in the reservoir that may lead to a bilinear flow regime can be modeled. In turbidite reservoirs, the degree of amalgamation, dimensions of lobe size, channel width, flow barriers in the form of cemented gravel lags or shale drapes and their coverage may affect well test data (Chen et al, 2012). The following geological features were modeled and its pressure behavior analyzed:…”
Section: Base Model Construction and Verificationmentioning
confidence: 99%
“…The backbone-cluster type of flow has been observed in laboratory experiments (Klemm et al, 1999). A turbiditic system (Chen et al, 2012) with communicating channels and appended lobes may also be approximated by the BB-SC description -in this case with different properties.…”
Section: Percolation Clustersmentioning
confidence: 99%